Arsenic(+3) and DNA methyltransferases, and arsenic speciation in tadpole and frog life stages of western clawed frogs (Silurana tropicalis) exposed to arsenate1. Issue 8 (5th August 2015) - Koch, Iris; Zhang, Jing; Button, Mark; Gibson, Laura A.; Caumette, Guilhem; Langlois, Valerie S.; Reimer, Kenneth J.; Cullen, William R.
<x xml:space="preserve">Abstract</x> Silurana tropicalis tadpoles and frogs exposed to arsenate exhibit changes in levels of methylating enzymes DNMT1 and AS3MT, and methylate arsenic to trimethylarsine oxide and tetramethylarsonium.